Concepts of Care in Organizational Crisis Prevention - Simola, Sheldene (Journal of business ethics, 2005)
The role of ethics in organizational crisis management has received limited but growing attention. However, the majority of research has focused on applications of ethical theories to managing crisis events after they have occurred, as opposed to the implications of ethical theories for the primary prevention of these situations. The relationship between concepts derived from a contemporary ethic of care (resistance, voice, silence, connection) (Gilligan, C.: 1988, ‘Exit–voice Dilemmas in Adolescent Development’, in C. Gilligan, J. V. Ward and J. M. Taylor (eds.) (Harvard University Press, Cambridge, MA), pp. 141–158, Gilligan, C.: 1990, ‘Preface’, in C. Gilligan, N. P. Lyons and T. J. Hanmer (eds.) (Harvard University Press, Cambridge, MA), pp. 6–29, Gilligan, C.: 1991, ‘Women’s Psychological Development: Implications for Psychotherapy’, in C. Gilligan, A. G. Rogers and D. L. Tolman (eds.) (Harrington Park Press, New York), pp. 5–32), and, concepts derived from a classic theory of organizational decline and recovery (exit, voice, loyalty) (Hirschman, A. O.: 1970, Exit, Voice, and Loyalty: Responses to Decline in Firms,Organizations, and States (Harvard University Press, Cambridge, MA)) is described. The relevance of these notions for signal detection and uptake in organizational crisis prevention is discussed. Implications for prevention are highlighted through consideration of a case involving organizational crisis, the explosion of the space shuttle Challenger. Directions for both business practice and future research are identified